Half moon Henry Hudson and the voyage that redrew the map of the New World - Hunter, Doug 1959- (Bloomsbury Press, 2009)
Recounts how Henry Hudson defied orders to find an eastern passage to China by redirecting his voyage along the coastline from Spanish Florida to the Grand Banks, an effort that laid a foundation for New York's establishment as a global capital.